Health Status and Economic Growth in Kenya - Kelvin Mutira Misango (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
Economic growth is important as it measures the prosperity of a nation which indeed increases the output per person and factors like human capital, physical capital and technological change which are the main drivers towards achieving economic growth. Kenya’s Vision projected an economic growth rate of 10 per cent per annum from 2008 to 2030 which has not been achieved to date. The purpose of this study was to analyze the impact of health status on economic growth in Kenya. The specific objectives of the study were to determine the effect of: nutrition status and life expectancy on economic growth in Kenya. The study adopted the endogenous growth theory and incorporated key health status into the model as a function of human capital. Research design employed was explanatory research design and relied on secondary data from World Bank from 1985 to 2018. Applying regression model, the results revealed that coefficient of life expectancy was 1.1556, which was positive and significant at 5 percent level. This implied that for every one percent increase in coefficient of life expectancy, GDP growth rate could increase by 1.1556 percent. Coefficient of nutrition status was -1.143, which was negative and insignificant at 5 percent level. This implied that for every one percent increase in coefficient of nutrition status, GDP growth rate would fall by 1.143 percent. Considering that increased life expectancy had direct effect on increase in economic growth rate, Kenya government could put in place policies promoting citizen’s health. Suitable social sector policies and government interventions are required to increase life expectancy and consequently economic growth rate. Further, there is also a need for involvement of health human force in macro and micro policy-makings and critically examine other determinant of health care expenditure